SP0096 EULAR/PRES standardised procedures for musculoskeletal ultrasound (MSUS) imaging in pediatric rheumatology. (15th June 2017) - Collado, P
Abstract : Musculoskeletal ultrasound (MSUS) is a readily available and suitable imaging technique to asses the immature skeleton of paediatrics in different musculoskeletal rheumatic diseases (MSRD). Besides the potential operator –dependent feature of this technique, the age-related variation of normal sonoanatomy due to the child's growth makes more difficult acquisition, interpretation and comparison of images than in adults. Hence, to use MSUS as a valid technique for diagnosis of MSRD, it is needed to develop specifically evidence-based recommendations for paediatrics. Additionally, the variability in background and experience of ultrasonographers in different countries requires an international multidisciplinary contribution for an optimal standardization of MSUS performance in paediatric MSRD. Reflecting the perceived need for developing recommendations on the standardization of procedures for performing MSUS examination in MSRD, a collaborative international EULAR/PReS task force was convened. In the talk, it is going to summarize the original proposed specific aims and update on work for each aim previously mentioned. A systematic literature search was performed in Medline and Embase from databases inception to 1st June 2016 as the first step. One hundred and eighty-eight articles were finally included after reviewing 6059 records identified. The scanning for the knee and the ankle joint was the most common reported, whereas the paediatric wrist was uncommon. Disclosure of Interest: None declared